Cutaneous manifestations of metastatic Crohn's disease. Issue 5 (28th June 2018) - Schneider, Samantha L.; Foster, Katherine; Patel, Devika; Shwayder, Tor
Abstract: Metastatic Crohn's disease is a rare cutaneous complication of primary Crohn's disease. It is a granulomatous inflammatory process, similar to the pathogenic mechanism of Crohn's disease, that occurs in sites discontiguous from the gastrointestinal tract. Metastatic Crohn's disease can precede the development of Crohn's disease by months to years, and children are more likely to present with metastatic Crohn's disease in the absence of gastrointestinal symptoms. Given that approximately 30% of individuals with Crohn's disease present in childhood, early recognition of extraintestinal manifestations of Crohn's disease such as metastatic Crohn's disease can aid in timely diagnosis and management of bowel disease. We present data from two pediatric cases of metastatic Crohn's disease recently seen at our institution in addition to the 61 reported cases of pediatric metastatic Crohn's disease in the literature. This review article will focus on the epidemiology, pathogenesis, clinical features, and histology of and treatment options for pediatric metastatic Crohn's disease.